An Examination of Reconstructionist Educational Philosophy from an Islamic Perspective and Its Relevance to Modern Developments - Agung Purnomo (Konsultan Jurnal Ilmiah Indonesia, 2025)
The background of this study stems from the need to reconstruct the paradigm of Islamic education to respond effectively to the challenges of modernization, globalization, and moral crisis. The philosophy of reconstructionism offers a concept of social renewal through education, which, in the context of Islam, can be integrated with the values of tawhid and justice. This research aims to examine in depth the relevance of reconstructionism from an Islamic perspective and its contribution to developing an educational system that is adaptive to contemporary developments. The study employs a qualitative method with a library research approach, analyzing academic literature, books, and journal articles related to Islamic educational philosophy and reconstructionist thought. Data were analyzed using content analysis through a descriptive-analytical framework. The findings reveal that reconstructionism shares a common orientation with Islamic education in terms of promoting constructive social transformation, although they differ in foundational principles. Islam emphasizes harmony between reason, revelation, and divine morality, while reconstructionism focuses on rationality and social progress. In conclusion, integrating both perspectives can produce a reconstructive Islamic education paradigm that is adaptive to advances in science and technology while remaining deeply rooted in spiritual and universal human values.